Influence of Effects of the Last World Financial and Economic Crisis on the Perspective of Knowledge-based Economy Development in Poland - Kuźniar, Katarzyna (Wpływ skutków ostatniego światowego kryzysu finansowego i gospodarczego na perspektywy rozwoju gospodarki opartej na wiedzy w Polsce, 2010)
The objective of the article is answering a question for opportunities to use the economic success of Poland, which resisted to the last global crisis, in order to accelerate the development processes in our state. In the first part of the paper the author focuses on the reasons of the crisis, its course and sources of the Poland's success. Then, the author characterizes the macroeconomic surrounding favorable to the knowledge-based economy and presents the directions of engagement of Polish authorities in the process of construction of national competitive advantage based on innovations.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 136, s. 83-91
Keywords: financial and economic crisis; macroeconomic conditionings of knowledge-based economy; national competitive advantage; internationalization of R&D